Description of male, pupa and larva of Psorophora (Grabhamia) paulli and redescription of the female (Diptera: Culicidae) - Stein, Marina; Rossi, Gustavo Carlos; Almirón, Walter Ricardo (Zootaxa, 2013)
The female of Psorophora (Grabhamia) paulli Paterson & Shannon is redescribed, and the pupa, fourth-instar larva and male genitalia are described and illustrated for the first time. Information about the distribution, bionomics and taxonomy is also included. Adults of Ps. paulli can be separated from the other species of the genus and subgenus by its small size. The larva of Ps. paulli is similar to that of Ps. varinervis Edwards and Ps. discolor (Coquillett) but can be separated based on the development of setae 1-X and 5-VIII, the length of the anal papillae and the comb on a sclerotized area.